Intelligent speech signal processing - Dey, Nilanjan 1984- (Academic Press, 2019)
Intelligent Speech Signal Processing investigates the utilization of speech analytics across several systems and real-world activities, including sharing data analytics, creating collaboration networks between several participants, and implementing video-conferencing in different application areas. Chapters focus on the latest applications of speech data analysis and management tools across different recording systems. The book emphasizes the multidisciplinary nature of the field, presenting different applications and challenges with extensive studies on the design, development and management of intelligent systems, neural networks and related machine learning techniques for speech signal processing.
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed March 29, 2019)
Keywords: Automatic speech recognition; Speech processing systems; Signals and signaling; Reconnaissance automatique de la parole; Traitement automatique de la parole; Signaux et signalisation; COMPUTERS; General